Arrangement of Agrarian Reform as A Basis For Providing Legal Certainty For the Community - Prakoso, Bhim; Hariyani, Iswi; Wahjuni, Edi; Wisnuwardhani, Diah Aju (PT Matra Cendikia Abadi, 2024)
The existence of government policies that have been issued regarding the implementation of the agrarian reform program but still give rise to imbalances in the structure of control, ownership, use, and utilization of land. Until now, it seems as if the implementation of the agrarian reform program is running in place, even though in order to make the agrarian reform a success, the government has tried to create regulations that are used as a legal basis so that the agrarian reform can run according to its objectives. This study aims to examine the legal certainty of agrarian reform asset management policies. This study is a normative study that uses a statutory regulatory approach and a conceptual approach. The statutory approach is a study of legal products. The results of the study show that 1). The nature of the arrangement of Agrarian Reform assets that are certain: Agrarian reform fundamentally provides programs that can resolve the problem of rural community poverty, increase welfare with national food independence, increase land productivity, provide recognition of land rights owned both privately, state, and public land whose use is to meet the interests of the community. 2). Implementation of land redistribution in Agrarian Reform: There are three forms of agrarian reform, namely asset legalization, land redistribution and social forestry. Model of equitable agrarian reform: Agrarian reform or equitable agrarian renewal is something that is complex and multidimensional which is a major program of the Indonesian state in realizing the welfare of the Indonesian people, especially in terms of increasing access for poor farmers to land control in Indonesia, but implementing equitable agrarian reform is not an easy thing, there are many obstacles, both in terms of legal aspects, land administration, social, political, cultural, and security. Keywords: Asset Management Policy, Agrarian Reform, Legal Certainty for the Community